ACCOUNTING FOR STOCK DIVIDENDS RECEIVED. - Kerrigan, Harry D. (The Accounting Review, 1938)
Abstract In considering the effect of a stock dividend upon its recipient it is first necessary to inquire into the fundamental meaning of the terms "income" and "capital," and the distinctions, if any, between income to the corporation and income to stockholders. With a working understanding of these matters in mind, it will then be possible to discuss the nature of stock dividends from the recipient's standpoint. Discussion of economic matters is frequently confused by a failure to distinguish between interpretations of a particular phenomenon in business practice and the underlying facts and principles of the phenomenon as interpreted by economists. The difference lies in the theoretical level at which underlying facts and principles necessarily are kept in the economist's analysis. The theoretical level is used because the assumptions upon which the reasoning rests may not obtain to the degree required for its validation on the practical level. And the economist's assumptions fall short of conformity to reality because they are virtually impossible of full verification.